Solving the location area problem by using differential evolution - Almeida-Luz, Sonia M. (Array, 2008)
Abstract: In mobile networks, one of the hard tasks is to determine the best partitioning in the Location Area problem, but it is also an important strategy to try to reduce all the involved management costs. In this paper we present a new approach to solve the location management problem based on the Location Area partitioning, as a cost optimization problem. We use a Differential Evolution based algorithm to find the best configuration to the Location Areas in a mobile network. We try to find the best values for the Differential Evolution parameters as well as define the scheme that enables us to obtain better results, when compared to classical strategies and to other authors’ results. To obtain the best solution we develop four distinct experiments, each one applied to one Differential Evolution parameter. This is a new approach to this problem that has given us good results